Особенности миграции чибиса (Vanellus vanellus) на западе Украины - Шидловский, И.В. (Вестник зоологии, 2001)
Установлено, что сроки прилета птиц зависят от характера прихода весны. В этот сезон наблюдается очень быстрый пролет чибисов в восточном, юго-восточном и, частично, в северо-восточном направлении (76,5% птиц летят на восток). Стаи птиц, летящие весной, обычно малочисленны, редко превышают 30 особей. Самая большая интенсивность этого пролета приходится на утреннее время - между 1 и 4 часами после восхода солнца (70-75% птиц). В основном птицы летят на высотах от 15 до 40 м. Для вида характерны летние миграции, которые наблюдаются во II половине мая - начале июня, происходят на малых высотах и имеют западное направление. Суточный пик этой миграции по сравнению с весенней смещен - основная часть птиц пролетают через 2-3 ч после восхода солнца. Осенняя миграция начинается в I декаде августа. Она характеризируется многочисленными и поливидовыми стаями. The data on migrations of Lapwing on the territory of western oblasts of Ukraine had been collected during 13 years. All information was gathered on the observation posts, catching and ringing station, and during expeditions. Terms of came flying of birds depend from the spring character. Rapid fly of the species in East, South-East and, particularly, in North-East directions (76,5% of birds fly in the East direction) was noted during spring season. Bird flocks, which fly in spring, are characterized by the low number of specimens, rarely more than 30 birds. The most intensive fly pass early in the morning – between the first and fourth hour after sunrise (nearly 70—75% of birds flies during that time). Most of birds flies on the 15—34 m height. Summer migrations are characteristic for the species. They pass in western direction on low heights from the second half of May till the beginning of June. Daily spike of this migration is dislocated in right comparing to the spring migration; most birds fly in 2—3 hours after sunrise. Autumn migration starts in the beginning of August. It is characterized by numerous and multispecific flocks.